Histopathological alterations in liver of Nile tilapia supplemented with selenomethionine - Gomes, Gabriela Roncada; Cruz, Claudinei da [UNESP]; Sakabe, Roberson; Ramos, Fabricio Menezes; Fujimoto, Rodrigo Yudi (Empresa Brasil Pesq Agropec, 2016)
The objective of this work was to evaluate the effects of selenomethionine supplementation on liver histopathology of Nile tilapia (Oreochromis niloticus). Selenomethionine was added to the base diet (without supplementation) at the concentrations of 0.25, 0.50, 1.0, and 1.50 mg kg(-1), which consisted of five treatments, with four replicates. After 90 days of experiment, hepatic lipid degeneration was observed in the liver of the animals that received diet without supplementation, indicating selenium deficiency. However, the animals that received above 1.0 mg kg(-1) showed hypertrophy, glycogen accumulation, cordonal disarrangement, foci of necrosis and lipid peroxidation in the liver. Selenium is essential for Nile tilapia nutrition; however, concentrations above 1.0 mg kg(-1) selenomethionine impair the liver metabolism.
Keywords: Oreochromis niloticus; hepatocytes; micronutrients; toxicity